Internet connectivity disruption in Bahrain (Bahrain) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Bahrain. Data sourced from IODA.
Network Disruption Incident ID: BH-2026-0034. Severity: critical. Confidence: 67%